Sharing and connecting information in the context of the Covid-19 pandemic and training skills for employees to meet the needs of businesses in digital transformation - Thi Hang Nguyen; Nguyen Tran Trong (Management)
In the context of the strong outbreak of the Covid-19 pandemic leading to increasing social distancing, it is difficult for businesses to access the labor market. Therefore, it is necessary to create a connection channel between the employer and the labor supplier. That helps to adapt to the context of the Covid-19 pandemic, while also taking advantage of the achievements from the Industrial Revolution 4.0. The development of a training model that connects human resource trainers with human resource users who are businesses is considered an important requirement in the context of the Covid-19 pandemic. The university-enterprise model demonstrates active cooperation and has a profound impact on teaching and scientific research activities in universities. Since then, constantly improving the quality of training to create labor products that meet the rigorous needs of enterprises. This study uses exploratory factor analysis methods to screen observations to analyze, evaluate and draw conclusions about the formation of a university-enterprise linkage model. Thereby helping to create a bridge in cooperation between universities and businesses. On that basis, propose solutions to promote cooperation between universities and businesses in the current Vietnamese conditions, contributing to creating high-quality labor for society, meeting the needs of digital businesses.